Signaling Pathway and Small-Molecule Drug Discovery of FGFR: A Comprehensive Review - Zheng, Jia; Zhang, Wei; Li, Linfeng; He, Yi; Wei, Yue; Dang, Yongjun; Nie, Shenyou; Guo, Zufeng (Frontiers in Chemistry, 2022)
Targeted therapy is a groundbreaking innovation for cancer treatment. Among the receptor tyrosine kinases, the fibroblast growth factor receptors (FGFRs) garnered substantial attention as promising therapeutic targets due to their fundamental biological functions and frequently observed abnormality in tumors. In the past 2 decades, several generations of FGFR kinase inhibitors have been developed. This review starts by introducing the biological basis of FGF/FGFR signaling. It then gives a detailed description of different types of small-molecule FGFR inhibitors according to modes of action, followed by a systematic overview of small-molecule-based therapies of different modalities. It ends with our perspectives for the development of novel FGFR inhibitors.